Pituitary Volumes Are Reduced in Patients With Alcohol Use Disorder - Gurok, Mehmet Gurkan; Tabara, Mehmet Fatih; Koc, Mustafa; Saritoy, Sumeyra; Baykara, Sema; Atmaca, Murad (Oxford Univ Press, 2023)
Aims To determine whether there is a difference in pituitary gland volumes in patients with alcohol use disorder compared to healthy people. Methods The subjects included in the study consisted of 15 individuals who met the criteria for alcohol use disorder according to the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM 5) diagnostic criteria based on the Structured Clinical Interview for DSM 5 and were admitted to Firat University School of Medicine, Department of Psychiatry, or were hospitalized, and 17 healthy controls. The volumes of pituitary were measured in subjects. Results Absolute pituitary gland volumes of patients with alcohol use disorder and healthy controls were compared in the analysis performed using the independent samples t-test. The mean volume of the patient group was significantly smaller than the healthy controls (58.02 +/- 7.24 mm(3) in patients with alcohol use disorder vs. 83.08 +/- 12.11 mm(3), P < 0.01), a difference which persisted after controlling for age, gender and total brain size. Conclusions Patients with alcohol use disorder in this study had smaller pituitary gland volumes compared to those of healthy control subjects. However, this study has limitations including small sample size and not adjusting for previous or current medication use or current anxiety and depression.
Keywords: Hippocampal Volume; Healthy-Men; Brain Volumes; Gland Volume; Adrenal Axis; Dependence; Deficits; Relapse; Morphometry; Trajectories